Health care–associated infections in patients with head and neck cancer treated with chemotherapy and/or radiotherapy. (5th October 2015) - Mirabile, Aurora; Vismara, Chiara; Crippa, Fulvio; Bossi, Paolo; Locati, Laura; Bergamini, Cristiana; Granata, Roberta; Resteghini, Carlo; Conte, Eutilia; Morelli, Daniele; Scarpellini, Paolo; Licitra, Lisa
ABSTRACT: Background: The incidence of health care–associated infections in patients with head and neck cancer receiving chemotherapy and/or radiotherapy (RT) is unknown. This retrospective study investigated the most common pathogens and their antibiotic sensitivity/resistance patterns in patients with head and neck cancer. Methods: Infection rates in patients with head and neck cancer were analyzed over 2 periods (January 2005 to December 2009 and January 2010 to November 2012). Results: In the first period, 140 health care‐associated infections were observed among 2288 admissions, mostly because of gram‐negative pathogens affecting the respiratory tract. In the second period, 212 health care‐associated infections were observed. An increase in antibiotic resistance was reported. Health care‐associated infections were more frequent with: male sex, age <65 years, important comorbidities, smoking, proton pump inhibitors (PPIs), prophylaxis, and/or central venous catheter (CVC), locally advanced disease, and chemotherapy/RT, especially after the third week of treatment. Conclusion: Health care‐associated infections increased over time, with corresponding increases in gram‐negative pathogens and resistant strains. Prevention and treatment protocols should be implemented in institutions treating patients with head and neck cancer. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E1009–E1013, 2016